English: Bahasa Indonesia - Farhan Baehaki; Yasser Wahyudin; Ryzal Perdana; Arlisya Siti Nurfajar; Zidni Irpan Syaripudin (Universitas Lampung, 2021)
Wells as a source of water that is commonly used by people in Indonesia are very dependent on the conditions of the surrounding environment. The presence of environmental pollution by waste will be very dangerous, especially if the waste contains heavy metals such as Cr(VI). The highly soluble nature of Cr(VI) allows the process of infiltration from the river into the well water. This study aims to analyze the content of Cr(VI) in the well water of residents around the Citarum River. Samples were taken from two areas that have the criteria for the level of pollution and the environment which is dense with industrial activity, with a total of ten wells spread over the area. The concentration measurement was carried out using an atomic absorption spectrophotometer at a wavelength of 357.9 nm. The results showed that the levels of Cr(VI) ion at Location 1 were in the range of 0.014 – 0.022 ppm so that it could still be used for daily activities because it was below the threshold value. At Location 2, there are six wells whose water is still suitable for use because the value of the Cr(VI) ion content is still below the threshold value. Meanwhile, the water in the other four wells contains Cr(VI) ion level that exceeds the threshold value, so it can be said that it is not suitable for daily use.